Happiness of Single Women in the Context of Modern Society - Tram, Bui Thi Huong (Darul Yasin Al Sys, 2025)
The pursuit of happiness has become a central theme in both academic inquiry and social policy, yet the lived experiences of single women—particularly within Confucian-influenced societies—remain understudied. This study explores how single women in Vietnam define and experience happiness in the context of rapid modernization, industrialization, and globalization, all of which have significantly reshaped family structures and gender dynamics. Based on qualitative data from 15 in-depth interviews conducted between April and August 2025, the study employs thematic analysis to examine how autonomy, economic independence, emotional well-being, and cultural expectations intersect in shaping perceptions of happiness. The findings reveal that happiness for single women is a fluid, context-dependent construct, integrating traditional norms of familial responsibility with contemporary aspirations for individuality and self-fulfillment. Despite structural inequalities and enduring social stigma, participants exhibited emotional resilience, financial agency, and a growing sense of empowerment. This study contributes to feminist sociology by situating women’s well-being within Vietnam’s broader socio-cultural transformation. It also offers practical implications for policies aimed at advancing gender equality, promoting social inclusion, and enhancing subjective well-being within the framework of sustainable development.